A carbon-based anode combining with SiOx and nanodiamond for high performance lithium ion battery. (October 2019) - Gao, Xuan; Sun, Xiaochen; Liu, Junsong; Gao, Nan; Li, Hongdong
Highlights: Nanodiamond is introduced into SiO x /carbon-based anode for improving the cycle stability and specific capacity of lithium ion batteries. The anodes with nanodiamond are prepared by a microwave procedure. The enhancement mechanism of high performance of LIBs is investigated based on the nanodiamond-related anode materials. Abstract: We report a novel anode consisting of detonation nanodiamond, SiO x nanoparticals and carbon nanosheets, to achieve high performance lithium-ion batteries. In the process of charge and discharge, the lithium ion batteries using the prepared nanocomposite anode show remarkable capacity performance with a specific capacity of 1182 mA h g −1 at a constant current of 100 mA g −1 after 100 cycles. With further increasing the current to 1000 mA g −1, a high specific capacity of 622 mA h g −1 can be realized after 750 cycles, indicating a superior long-term cycle stability. The improvement of cycle stability and specific capacity can be attributed to the introduction of nanodiamond to form an effective buffer structure and efficient Li + transport pathway.